Analisis Atas Lembaga Wakaf Dalam Menjalankan Wakaf Produktif Pada Yayasan Dompet Dhuafa - Ali Idrus (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2020)
ABSTRACTThis study aims to determine the form of the waqf program of the Dompet Dhuafa foundation in carrying out productive waqf and the challenges faced in carrying out productive waqf. The waqf institution that is used as data in this study is Dompet Dhuafa which is a pioneer of waqf in Indonesia. The results showed that the Dompet Duafa Foundation is divided into cash waqf, immovable assets, movable assets. All models are distributed into 5 pillars, namely education, health, economy, social, and preaching and culture programs.Keywords : Productive Waqf, Productiv Waqf Model, and Dompet Dhuafa.